2018
DOI: 10.1186/s40643-018-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deep eutectic solvents on the asymmetric hydrolysis of styrene oxide by mung bean epoxide hydrolases

Abstract: Background: Deep eutectic solvents have attracted considerable attention in numerous fields. There is little information on mung bean epoxide hydrolase-catalyzed epoxides in deep eutectic solvent-containing system. Results:Adding deep eutectic solvents with hydrogen bond donor of acids to phosphate buffer resulted in an obvious decrease in the optical purity of product; nevertheless, the relative slight change was observed by the addition of the deep eutectic solvents with hydrogen bond donor of alcohols and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…21 In a styrene oxide hydrolysis reaction catalyzed by epoxide hydrolases, the addition of the DESs ChCl/oxalic acid, ChCl/levulinic acid, ChCl/malonic acid, ChCl/malic acid, or ChCl/citric acid completely inhibited the enzymatic hydrolysis. 37 Similar inhibition by ChCl/malonic acid has been observed in the process of isoquercitrin production by recombinant E. coli whole cells. 38 Moreover, Peng et al believed that the DES caused a cell wall expansion, which made the intracellular catalyst more sensitive to pH changes and malfunctioning in the biotransformation procedure, 22 inferring that the acid−base property of the DES should be considered when the solvent is used in a pH-sensitive catalysis process.…”
Section: ■ Results and Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…21 In a styrene oxide hydrolysis reaction catalyzed by epoxide hydrolases, the addition of the DESs ChCl/oxalic acid, ChCl/levulinic acid, ChCl/malonic acid, ChCl/malic acid, or ChCl/citric acid completely inhibited the enzymatic hydrolysis. 37 Similar inhibition by ChCl/malonic acid has been observed in the process of isoquercitrin production by recombinant E. coli whole cells. 38 Moreover, Peng et al believed that the DES caused a cell wall expansion, which made the intracellular catalyst more sensitive to pH changes and malfunctioning in the biotransformation procedure, 22 inferring that the acid−base property of the DES should be considered when the solvent is used in a pH-sensitive catalysis process.…”
Section: ■ Results and Discussionsupporting
confidence: 58%
“…Yang et al found that the presence of an organic acid based DES triggered an abrupt pH drop in the reaction solution that gave the poorest yield among those DESs tested . In a styrene oxide hydrolysis reaction catalyzed by epoxide hydrolases, the addition of the DESs ChCl/oxalic acid, ChCl/levulinic acid, ChCl/malonic acid, ChCl/malic acid, or ChCl/citric acid completely inhibited the enzymatic hydrolysis . Similar inhibition by ChCl/malonic acid has been observed in the process of isoquercitrin production by recombinant E.…”
Section: Resultsmentioning
confidence: 75%
“…For example, epoxide hydrolases (EHs) are widely used for epoxide hydrolysis for the synthesis of enantiopure epoxides and vicinal diols, which are vital multipurpose building blocks for diverse pharmaceuticals [179]. In several studies, the application of various DESs was exploited to overcome the poor solubility of epoxides and non-enzymatic hydrolysis (Table 2, entries 1 and 2) [163,180,181]. Intriguingly, the regioselectivity of potato EHs toward the hydrolysis of a chiral (1,2)-trans-2-methylstyrene oxide was altered in the presence of 40 vol.% ChCl-Gly (1:2), while the K M was elevated 20-fold [163].…”
Section: Hydrolase-meditated Api Syntheses In Dessmentioning
confidence: 99%
“…Moreover, the influence of the single components of DESs was investigated by the authors: glycerol and ethylene-glycol are able to significantly enhance the activity of the enzyme, as opposed to choline chloride, probably because of a concomitant enzyme-mediated transglycosylation reaction. Peng et al [ 58 ] studied the influences of various amounts of DESs on mung bean epoxide hydrolase in phosphate buffer at 35 °C. For example, the addition of 10% v / v of ChCl/triethylene glycol (1:4) caused an improvement in the enantiopurity of product from 83 ± 1.3% to 88 ± 0.3%.…”
Section: Hydrolysismentioning
confidence: 99%